Actividad antibacteriana de dos especies del género Couroupita frente a cinco bacterias patógenas. Iquitos, 2023 - Chávez Buendía, John Arlis (2025)
The study determined the in vitro antibacterial activity of ethanolic extracts of leaves and fruits of Couroupita guianensis and Couroupita subsessilis against pathogenic bacteria from Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 15442, Klebsiella pneumoniae ATCC 13883 and Salmonella typhimurium ATCC 14028. The study had a quantitative-experimental approach that included phytochemical screening and bacterial sensitivity tests using Kirby-Bauer disk diffusion and minimum inhibitory concentration (MIC) methods. Phytochemical screening resulted in both plant species showing abundance of carotenes, alkaloids and saponins. The results showed that the leaf extract of C. guianensis presented inhibition halos of 7 mm to 7.5 mm on S. aureus, while C. subsessilis leaf extract showed inhibition halos of 7.3 mm to 10.7 mm for E. coli; and the fruit extract presented inhibition halos of 7 mm to 9.4 mm for E. coli and S. typhimurium in both cases below the values of the established categories. In conclusion, none of the species had antibacterial activity compared to the reference antibiotics, the study highlights the potential of Couroupita species as a source of bioactive compounds, suggesting future research to optimize their therapeutic properties.